An isosceles triangle with base
a
and the lateral side
b
, and an isosceles triangle with base
b
and the lateral side a are inscribed in a circle of radius
R
, given that
a
=
b
, then evaluate
R
2
a
b
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes! That's the first thing I noticed too.
Very nice and amazing solution.
The formula of a triangle's circumradius given its sides x , y , z can be expressed as: 2 ∗ ( x 2 y 2 + x 2 z 2 + y 2 z 2 ) − x 4 − y 4 − z 4 x y z
Let R 1 be the radius of the circumcircle of the triangle with sides ( a , b , b ) , and define R 2 analogously for the triangle of sides ( a , a , b ) . Assume, WLOG, that a > b ; the result that will be derived from here doesn't depend on whether a > b because it will be, in a sense, symmetrical.
Using the formula I've shown above, let us calculate R 1 and R 2 .
R 1 = 4 b 2 − a 2 b 2
R 2 = 4 a 2 − b 2 a 2
Since R 1 = R 2 , we can write:
4 b 2 − a 2 b 2 = 4 a 2 − b 2 a 2
Squaring both sides and multiplying the factors yields:
4 a 2 b 4 − b 6 = 4 a 4 b 2 − a 6
Rearranging the terms and factoring conveniently:
a 6 − b 6 = 4 a 2 b 2 ∗ ( a 2 − b 2 )
( a 2 − b 2 ) ∗ ( a 4 + a 2 b 2 + b 4 ) = 4 a 2 b 2 ∗ ( a 2 − b 2 )
Since we know that a = b , we can divide both terms by ( a 2 − b 2 ) to obtain the following result:
a 4 + a 2 b 2 + b 4 = 4 a 2 b 2
a 4 − 3 a 2 b 2 + b 4 = 0
Divide both sides by b 4 and let us define t = b a .
Then, we will obtain the following equation:
t 2 − 3 t + 1 = 0
Solving for t yields the solutions 2 3 ± 5 , which happen to be the square of the golden ratio and its inverse (namely ϕ 2 and ϕ − 2 ). Since we've assumed that a > b , we can conclude that a = ϕ b . Had we assumed the opposite, we would have used the other root we've found.
Substituting a = ϕ b back in the formula for R :
R = 4 b 2 − ϕ 2 b 2 b 2
Thus:
R 2 = 4 b 2 − ϕ 2 b 2 b 4 = 4 − ϕ 2 b 2 .
Now we have all of the information we need in order to calculate R 2 a b :
R 2 a b = 4 − ϕ 2 b 2 b ∗ ( ϕ b ) = ϕ ∗ ( 4 − ϕ 2 ) = ( 5 ) ≈ 2 . 2 3 6
A different approach than usual . Thanks for sharing this new method .
Apart from the solution I have posted, I too have used this method slightly differently.
s
1
∗
(
s
−
a
)
(
s
−
b
)
2
a
b
2
=
R
=
s
2
∗
(
s
−
a
)
2
(
s
−
b
)
a
2
b
w
h
e
r
e
2
s
1
=
a
+
2
b
,
2
s
2
=
2
a
+
b
.
You probably can figure this out from looking at this graphic
Define b>a, when we rotate so that base b coincides with side b, recognize this as a regular pentagon in a circle radius 1, with side length a. The product ab is (2cos54)(2/sec18) or 2.2359
Great observation! The regular pentagon occurs with two copies of the triangle being added on.
Thank you!
a b/ R^ 2 = Sqrt (5) = 2.2360679774997896964091736687313
Sketch {a, a, b} of side a longer than side b on a circle. Then, sketch {b, b, a} on one side of side a. Label angle B and then angle A according to most usual convention of opposite to b and opposite to a respectively.
Quadrilateral with angle A implies for two angles of (180 d - A) on the first isosceles triangle sketched. Therefore, 2 (180 d - A) + B = 180 d. Rearrange equation:
180 d - A = A - B
Taking Cosine onto both sides,
Cos (180 d - A) = Cos (A - B)
-Cos A = Cos A Cos B + Sin A Sin B
Cos A (1 + Cos B) + Sin A Sin B = 0
Cos B = (a^2 + a^2 - b^2)/ (2 a^2) = (2 a^2 - b^2)/ (2 a^2) while
Cos A = (b^2 + b^2 - a^2)/ (2 b^2) = (2 b^2 - a^2)/ (2 b^2).
Forming right angle triangles for finding values of Sin B and Sin A,
[2 a^2 - b^2, b Sqrt (4 a^2 - b^2), 2 a^2] for B and
[2 b^2 - a^2, a Sqrt (4 b^2 - a^2), 2 b^2] for A all by Pythagoras' theorem.
Sin A = a Sqrt (4 b^2 - a^2)/ (2 b^2) and Sin B = b Sqrt (4 a^2 - b^2)/ (2 a^2)
Substitutes Cos A, Cos B, Sin A and Sin B into Cos A (1 + Cos B) + Sin A Sin B = 0:
(1 - 0.5 a^2/ b^2)(2 - 0.5 b^2/ a^2) + [a Sqrt (4 b^2 - a^2)/ (2 b^2)][b Sqrt (4 a^2 - b^2)/ (2 a^2)]
Denominators (2 a^2)(2 b^2) can be eliminated:
(a^2 - 2 b^2)(4 a^2 - b^2) = a b Sqrt [(4 b^2 - a^2)(4 a^2 - a^2)]
Since (4 a^2 - b^2) = Sqrt (4 a^2 - b^2) Sqrt (4 a^2 - b^2),
(a^2 - 2 b^2) Sqrt (4 a^2 - b^2) = a b Sqrt (4 b^2 - a^2)
(a^4 - 4 a^2 b^2 + 4 b^2)(4 a^2 - b^2) = (a b)^2 (4 b^2 - a^2)
4 a^6 - 16 a^4 b^2 + 16 a^2 b^4 - 4 b^6 = 0
a^6 - 4 a^4 b^2 + 4 a^2 b^4 - b^6 = 0 {The most critical equation of this question.}
(a^2 - b^2)(a^4 - 3 a^2 b^2 + b^4) = 0
(a^2 - b^2)[a^2 - (3 + Sqrt (5))/ 2 b^2] [a^2 - (3 - Sqrt (5))/ 2 b^2]= 0
For a to b of positive ratios only,
a = b OR
a = Sqrt [(3 + Sqrt (5))/2] b = [(Sqrt (5) + 1)/ 2] b = 1.6180339887498948482045868343656 b OR
a = Sqrt [(3 - Sqrt (5))/2] b = [(Sqrt (5) - 1)/ 2] b = 0.6180339887498948482045868343656 b
Since a <>b and a > b, while only two biggest isosceles triangles are concerned,
a = [(Sqrt (5) + 1)/ 2] b = 1.6180339887498948482045868343656 b is the only one.
Cos B= 1 - 0.5 (b/ a)^2
B = 36 d
Triangle with vertex center O and same side angles as {a, a, b} is 72 d. Half of it forming two right angle triangles with angle 36 d at center O.
Let R = 1 unit for convenience of finding ratios,
R Sin 36 d = 0. 5 b
b = 2 R Sin 36 d = 2 Sin 36 = 1.1755705045849462583374119092781
a = (1.6180339887498948482045868343656) (2 Sin 36)
a b / R^2 = (1.6180339887498948482045868343656) (2 Sin 36)^2
a b / R^2 = 2.2360679774997896964091736687313 = Sqrt (5)
With all due respect sir, please use LaTEX in your solution
Problem Loading...
Note Loading...
Set Loading...
If we draw the first isosceles triangle, then use both lateral sides as the bases for isosceles triangles with lateral sides length a , (with sides external to the first triangle), then the convex hull we have formed is a regular pentagon with sides length a .
The radius of the circle in which this regular pentagon is inscribed is
R = 2 sin ( 3 6 ∘ ) a ,
and the chord that corresponds to side/base b has length
b = 2 cos ( 7 2 ∘ ) a .
Thus R 2 a b = 4 sin 2 ( 3 6 ∘ ) a 2 2 cos ( 7 2 ∘ ) a 2 = cos ( 7 2 ∘ ) 2 sin 2 ( 3 6 ∘ ) = sec ( 7 2 ∘ ) − 1 = 5 = 2 . 2 3 6
to 3 decimal places.